Multi-functional 3D honeycomb ceramic plate for clean water production by heterogeneous photo-Fenton reaction and solar-driven water evaporation. (June 2019) - Shi, Le; Shi, Yusuf; Zhuo, Sifei; Zhang, Chenlin; Aldrees, Yara; Aleid, Sara; Wang, Peng
Abstract: The application of solar-driven water evaporation process in clean water production via solar distillation is recently intensively investigated. The phase change and mass transfer processes during the solar-driven water evaporation process can directly leave behind the salts, heavy metals, organic dyes, etc and simultaneously produce the clean water vapor. However, if the water source is contaminated by volatile organic compounds (VOCs), solar-driven water evaporation may accelerate VOCs volatile and enrich them in the condensate. In this work, the enrichment of VOCs in distillate water was first demonstrated and a multi-functional honeycomb ceramic plate was fabricated by coating a layer of CuFeMnO4 on the surface of a cordierite honeycomb ceramic substrate. The honeycomb structure was beneficial for light trapping and energy recycling and thus to improve the solar-to-water evaporation efficiency. The CuFeMnO4 coating layer acted as both the photothermal material for solar-driven water evaporation process and the catalyst for VOCs removal via heterogeneous photon-Fenton reaction. With the integration of photo-Fenton reaction into the solar distillation process, the clean distillate water was produced with efficient removal of the potential VOCs from the contaminated water sources. Graphical abstract: In the multi-functional honeycomb ceramic plate, the CuFeMnO4 coating layer acted both as the photothermal material for solar-driven water evaporation process and the catalyst for the heterogeneous photo-Fenton reaction. The honeycomb structure increased the solar light trapping. The VOCs in the polluted water source were efficiently removed by using this multi-functional honeycomb ceramic during the solar distillation operation.Image 1 Highlights: The 3D honeycomb structure is beneficial for light trapping and energy recycling. The CuFeMnO4 layer has good performance in both solar-driven water evaporation and heterogeneous photo-Fenton reaction. The first demonstration of VOCs enrichment issue in the clean water production via solar distillation. VOCs in distillate water can be efficiently removed by multi-functional CuFeMnO4 coated honeycomb ceramic material.